KOMUNIKASI PEMBELAJARAN MELALUI VIRTUAL LEARNING: (Studi Pada Matakuliah Public Speaking Univesitas Negeri Surabaya) - Vinda Maya Setianingrum (Universitas Islam Balitar, 2019)
The development of communication technology has affected in all aspects of life including education. Changes and adaptations should be done because the facilities of technology can make all human activities easier. The efforts have be done include improving the quality of education by implementing V-learning strategies in college. One of them is The Learning Strategy of Public Speaking Courses using classroom action method. The study performs phase 1 cycles and 2 cycles with identification, scaffolding, action, observation, and reflection. The final result of this research is the learning Model of Public Speaking courses with V-learning which can be accessed not only by students of Surabaya State University, but it can be followed by the students across study programs from other campuses. Based on 21 century skills that speaking skills need to be continuously developed to advance quality in all areas of work.